Procurement Governance Hypothesis Testing in a Proposed e-Procurement Implementation Assessment Model Framework - Rashid, Md. Abdur; Shorif Uddin, Mohammad (European Journal of Applied Sciences, 2024)
Purpose: This paper examines the critical factors that lead to the effective deployment of an electronic procurement system in Bangladesh. Developing an effective model for e-procurement implementation assessment is another objective. Design, methodology, and approach: Survey data from 206 samples of procurement entity (PE) officers obtained through primary investigation is used to operationalize the proposed model. Data from eleven zones in Bangladesh’s Roads and Highways Division (RHD) population were gathered using survey questionnaires. Findings: According to the analysis, the conceptual framework for the e-procurement assessment model that has been suggested is an affirmation that the procurement governance was approved. The findings also showed that the alternative hypothesis was accepted, indicating that the proposed model fit the data. Originality/value: This study represents the first effort to develop the theoretical framework for a specially developed and proposed model of e-procurement implementation assessment. The results of the study will benefit practitioners of e-procurement. The proposed assessment model will also support the subsequent review, implementation, and modification of enhanced e-GP policies and guidelines.